Analysis of Physiological Respiratory Variable Alarm Alerts Among Laboring Women Receiving Remifentanil. Issue 4 (December 2017) - Weiniger, C.F.; Carvalho, B.; Stocki, D.; Einav, S.
Abstract : ( Anesth Analg. 2017;124(4):1211–1218) Remifentanil is a short-acting opioid. Its use for labor analgesia is controversial because of reports of associated apnea. The aim of this study was to perform a secondary analysis of respiratory data from a previous study of laboring women using patient-controlled intravenous (IV) remifentanil analgesia, in order to evaluate physiologic variables as early warning alerts of apnea.